HUBUNGAN AJARAN TAREHAT QADARIYAH WAN NAQSABANDIYAH DENGAN PERILAKU EKONOMI - Nanat Fatah Natsir (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2001)
Religion and Economic Behavior (The Relationship Of Tarekat Qadiriyah Wan Naqsabandiyah With The Economic Activity In Pesantren Suryalaya, Tasikmalaya West Java, Indonesia).The goals of the reserarch are (1) to study the values of the teaching of Tarekat Qadiriyah Wan Naqsabandiyah that can influence the economic activity, and (2) to study the relationship of one's (concentration of) understanding of Tarekat Qadiriyah Wan Naqsabandiyah with one's economic activity. The research has been done in the center of Tarekat Qadiriyah Wan Naqsabandiyah that is in Pesantren Suryalaya, West Java.Tarekat Qadiriyah Wan Naqsabandiyah which is centralized in Pesantren Suryalaya, is the combination of two teaching of Tarekat. They are Tarekat Qadiriyah Wan Naqsabandiyah. The teaching of Tarekat Qadiriyah Wan Naqsabandiyah is based on the teaching of al-Qur'an, Hadits, ljma and Qiyas. The aims of Tarekat Qadiriyah Wan Naqsabandiyah are taqarrub to Allah; to reach mardhatillah; mabbah and ma'rifah to Allah.Tarekat Qadiriyah Wan Naqsabandiyah is now led by a mursyid/ leader/teacher, he is K.H.A. Shahibul Wafa Tajul Arifin (Abah Anom).If the economic activities which are by the followers of Tarekat Qadiriyah Wan Naqsabandiyah are observed there can be found a significant relationship between one's knowlege understanding of Tarekat Qadiriyah Wan Naqsabandiyah and his/her economic activities.That is why, there is a clear/significant relationship bet ween the level of one's knowledge of Tarekat Qadiriyah Wan Naqsabandiyah and their attitudes in working.There is a significant relationship between one's (orientation of) understanding of Tarekat Qadiriyah Wa Naqsabandiyah, in this case is involvement in their economic activities.There is significant relationship between one's understanding of Tarekat Qadiriyah Wan Naqsahandiyah, in this case is the teaching of zuhud and the degree of their involvement in their economic activities.There is a significant relationship between one's understanding of Tarekat Qadairiyah Wan Naqsabandiyah, in this case is the understsnding of Taqdir and their involvement in their economic activities.Thus, for those of the who follow Tarekat Qadiriyah Wan Naqsabandiyah whose level of knowledge of this Tarekat and whose orientation of their understanding of their religion is modern, the concept of working, more specifically the comercial activities, is not morely an sacred work that has the connection with their belief that can be found in Tarekat Qadariyah Wa Naqsabandiyah. Keyword: Religion, Economi, Behaviour, Relationship.